2020
DOI: 10.1016/j.cjco.2020.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Early Observations During the COVID-19 Pandemic in Cardiac Catheterization Procedures for ST-Elevation Myocardial Infarction Across Ontario

Abstract: In response to the COVID-19 pandemic, Ontario issued a declaration of emergency, implementing public health interventions on March 16, 2020. We compared cardiac catheterization procedures for STEMI between January 1 and May 10, 2020 to the same timeframe in 2019. From March 16 to May 10, 2020, after implementation of provincial directives, STEMI cases significantly decreased by up to 25%. The proportion of patients achieving guideline targets for FMC-balloon for PPCI decreased substantially to 28% (Median 101 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
2
13
1
Order By: Relevance
“…16 , 17 Current guidelines in the province of Ontario advocate maintaining a pPCI approach during COVID-19. 19 A previous Ontario-wide study of pPCI during COVID-19 showed increases in D2B times for patients triaged from the field, however our study did not 1 . This is likely based on the pre-emptive modifications to our system to avoid delays.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…16 , 17 Current guidelines in the province of Ontario advocate maintaining a pPCI approach during COVID-19. 19 A previous Ontario-wide study of pPCI during COVID-19 showed increases in D2B times for patients triaged from the field, however our study did not 1 . This is likely based on the pre-emptive modifications to our system to avoid delays.…”
Section: Discussioncontrasting
confidence: 63%
“…The reduction of STEMI admissions observed in Ottawa is similar to data from the province of Ontario, which demonstrated between a 18-25% reduction in STEMI cases. 1 The nadir of our STEMI admissions occurred between March 17 th – April 16 th , the period of peak COVID-19 incidence during the Ontario lockdown. Subsequently, the mean cases per month gradually rose into the re-opening time period, when incident COVID-19 cases began to fall, and public health restrictions were lifted.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While not all centres have reported increased DTB time during the pandemic [ 13 , 14 ] DTB delays have been the dominant trend. A registry of European countries [ 15 ], analysis of hospitals across the US [ 16 ] and China [ 17 ], a Canadian provincial study [ 18 ] and a global meta-analysis [ 19 ] all found that STEMI cases decreased while delays to reperfusion increased.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that these patients tended to avoid hospital visits even in true medical emergencies. [3][4][5][6] Because of these issues, the American Heart Association recommended that medical providers emphasize the importance of calling for help as soon as possible in the event of a CVD emergency. 7 Despite these challenges, there have been few investigations of patients' perspectives regarding these concerns.…”
mentioning
confidence: 99%